Strategi Peningkatan Pendapatan Petani Karet (Hevea Brasilinsies) yang dipengaruhi Fluktuasi Harga di Desa Lubuk Rengas Kecamatan Rantau Bayur Kabupaten Banyuasin - Apriyani, Septi; Jayanti, Nirmala; Nearti, Yuwinti (Jurnal Ilmiah Pertanian dan Peternakan, 2025)
Purpose: This study examines the impact of rubber price fluctuations on the income and welfare of rubber farmers in Lubuk Rengas Village, Rantau Bayur Subdistrict, Banyuasin Regency, and identifies strategies to increase income amid market uncertainties. Methodology/approach: Using a mixed methods approach, qualitative and quantitative data were collected from 35 farmers through questionnaires. Spearman correlation was applied to assess the relationship between price fluctuations and income, while SWOT analysis identified strategic options. Results/findings: The results show a strong, significant correlation between price fluctuations and farmers’ income (r = 0.831, p < 0.001). Key strategies include adopting pest-resistant clones, rejuvenating old plants, diversifying with intercropping and livestock, and enhancing farmer skills. Institutional support—through better financing access and private sector partnerships—is essential, while SWOT analysis highlights the need to maximize strengths and opportunities and mitigate weaknesses and threats like price volatility and climate change. Conclutions: Price fluctuations significantly affect farmers’ income, requiring sustainable, integrated strategies supported by institutional collaboration to safeguard and improve welfare. Limitations: The small sample size and single-location focus may limit generalizability; the cross-sectional design does not capture long-term trends. Contribution: This study provides empirical evidence on the link between commodity price volatility and farmers’ income, offering practical strategies and policy recommendations for resilience in volatile markets